THE IMPACT OF UZBEK CULTURAL NORMS ON ENGLISH PRAGMATIC COMPETENCE - Abdulxayeva, Maftunabonu (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article examines the impact of Uzbek cultural norms on the development of pragmatic competence in English as a foreign language. Pragmatic competence refers to the ability to use language appropriately according to context, social relations, and communicative intent. Drawing on theories of intercultural pragmatics and politeness, the paper analyzes how collectivism, respect for hierarchy, indirectness, and hospitality influence Uzbek learners’ English communication. The study argues that pragmatic transfer can result in both effective politeness strategies and pragmatic failure. Pedagogical implications for English language teaching in Uzbekistan are discussed, emphasizing explicit pragmatics instruction and intercultural awareness. The article also argues that pragmatic competence does not develop automatically alongside grammatical proficiency and so it requires explicit pedagogical attention, pragmatic competence as a main component of communicative competence, the study contributes to the second language acquisition (SLA) research and offers practical implications for improving the effectiveness of EFL instruction in culturally diverse contexts.